APPMAR 1.0: A Python application for downloading and analyzing of WAVEWATCH III® wave and wind data. (May 2022) - Rivillas-Ospina, German; Casas, Diego; Maza-Chamorro, Mauro Antonio; Bolívar, Marianella; Ruiz, Gabriel; Guerrero, Roberto; Horrillo-Caraballo, José M.; Guerrero, Milton; Díaz, Karina; Rio, Roberto del; Campos, Erick
Abstract: This work presents APPMAR 1.0, an application written in the Python programming language that downloads, processes, and analyzes wind and wave data. This application is composed of a graphical user interface (GUI) that contains two main modules: the first module downloads data from WAVEWATCH III® (WW3) production hindcasts by the National Oceanic and Atmospheric Administration (NOAA); the second module applies statistical mathematics for processing and analyzing wave and wind data. This application provides useful graphical results that describe mean and extreme wave and wind climate. APPMAR generates plots of exceedance probability, joint probability distribution, wave direction, Weibull distribution, and storm frequency analysis. Currently, APPMAR only downloads and analyzes wave and wind data from WW3 hindcasts, but it is under development to other datasets and marine climate parameters. This application has been tested in the Magdalena River mouth, Colombia, and Cancún, México, where observational wave and wind data are scarce. Highlights: Free and open-source Python application for wave and wind climate analysis. Downloads data from WAVEWATCH III hindcast. Performs mean and extreme climate analysis. Provides a GUI to improve interaction with the user. Especially useful on regions of limited data availability.